Design methodology of a reduced-scale test bench for fault detection and diagnosis. (November 2017) - Esteban, E.; Salgado, O.; Iturrospe, A.; Isasa, I.
Abstract: Condition monitoring is a crucial task for electromechanical system reliability and quality enhancement, which leads to early electrical and mechanical faults detection. In this paper, the design of a scaled test bench including its main subsystem components at initial stage is presented for the assessment of new methods dedicated to electrical and mechanical faults detection and diagnosis in electromechanical systems. In this paper a design methodology is proposed for developing a reduced-scale test bench dedicated to condition monitoring. Dimensional analysis is applied for ensuring the similarity between the scaled test bench and the full-size systems to be emulated. In addition, the scaled test bench includes the required instrumentation as well as an acquisition platform for development of condition monitoring strategy to batch condition monitoring of full-size systems. Finally, the similarity is evaluated by comparing both the simulation and the experimental results.